KAPASITAS ANTIOKSIDAN SENYAWA GOLONGAN TRITERPENOID PADA DAUN PRANAJIWA (Euchresta horsfieldii lesch benn) - Ayu Intan Sari, Kadek; Gede Gunawan, I Wayan; Dharma Putra, Ketut Gede (Jurnal Kimia (Journal of Chemistry); Vol. 9, no. 1 Januari 2015, 2015)
Isolation, identification, and anti-oxidant assay of triterpenoid compound  from Euchresta horsfieldii lesch benn) have been conducted. Maseration of 600 g pranajiwa leaves powder with n-hexane produced 6,1 g n-hexane extract which gave yellow to purple colour change with Lieberman-Burchard reagent. The separation with column chromatography using silica gel 60 obtained 3 fractions (F1, F2, F3) which were then analyzed with triterpenoid test. The positive fraction of triterpenoid (F1) produced 2 g yellow isolate. Infrared spectra indicated that the isolate was a triterpenoid, with characteristic functional groups of OH, –CH, C=O, –C=C, –CH 2 , –CH 3 , and C–O alcohol. Ultraviolet-visible spectra showed broad peak at 217 nm. The result of anti-oxidant capacity test of triterpenoid was 94,67%, showing that triterpenoid from pranajiwa leaves can be use as an anti-oxidant.
Keywords: Antioxidant Capacity, Euchresta horsfieldii lesch benn, Triterpenoid